A PSYCHOANALYSIS OF PSYCHOPATHS: PERSONALITY DISORDER OF THE MAIN CHARACTER IN ORPHAN FILM - Tira Nur Fitria (Jurusan Sastra Indonesia, 2022)
The objective of this research is to know the psychopath behavior shown by Esther as a main character in the Orphan film and the cause of her psychopath behavior. This research is descriptive qualitative research by using the psychopath's theory from Hare (2011). Orphan is a psychopathic, thriller, and psychological-themed film directed by Jaume Collet Serra which was released in 2009. The result analysis shows that in the film Orphan, Esther shows a psychopath behavior as the main character, they are: 1) displays a false or superficial self-charm, 2) Failure to conform to social norms (likely to breach social and legal standards and conventions), 3) Having unstable ad uncontrolled emotion, 4) Acting reckless, impulsive, and hard to control, 5) Heartless and lacks empathy, 6 )Lack of remorse, easy to lie for no reason and without guilt (deception), 7) Tending to seek the attention of others, 8) Capable of committing various types of criminal acts such as killing Sister Abigail, burning Max, trying to kill Max, stabbing John, shooting and stabbing Kate, 9) Behave aggressively, 10) Manipulative and likes to cheat, and 11) Having a history of being difficult, criminal, or dangerous experience. The cause of Esther’s psychopath is caused by a hormone disorder called hypopituitarism. It likes a body disorder. She looks like a 9-year-old physically, but psychologically she is normal as a 33-year-old woman, with feelings of liking for the sex and having biological needs. It can be seen from his attitude that always tries to be close to the father of his adoptive family, namely when he dresses up as an adult and then teases Jack, his adoptive father.